PEMBUATAN WEBSITE PROFIL SEKOLAH DI SMPN 1 BOJONGGEDE SEBAGAI ETELASE PRESTASI DAN MEDIA INFORMASI DIGITAL - Abdul Aziez Awal Saputra; Faturrahman Ikhsan Amin; Keisandy Dafa Mulianda; Muhammad Fatih Amri; Rayhan Maullana Brewiratama; Ryan Hidayat; Yeskarwani Gulo (Abdi Jurnal Publikasi, 2026)
The rapid transition to the Society 5.0 era demands educational institutions to adapt to digital-based information openness. SMP Negeri 1 Bojonggede, despite having a solid academic reputation and numerous student achievements, faces significant challenges in digital visibility. Currently, information dissemination relies on conventional methods such as physical notice boards and instant messaging groups, which are limited in reach and ineffective for public branding. This community service aims to bridge this gap by developing a professional school profile website as a digital showcase of achievements and a centralized information medium. The development method used is the Waterfall software engineering model, which includes requirements analysis, system design, coding implementation, and testing. The result of this activity is the availability of a responsive website accessible at smpn1bojonggede.sch.id, equipped with a comprehensive Content Management System (CMS). Furthermore, technical training for school staff has been conducted to ensure the sustainability of content management. This digitalization initiative successfully transforms the school's promotional flow, allowing for wider, real-time, and structured public access to information.